1972
DOI: 10.1063/1.1654255
|View full text |Cite
|
Sign up to set email alerts
|

Phase-matched submillimeter wave generation by difference-frequency mixing in ZnGeP2

Abstract: Using two step-tunable CO2 lasers, we have observed phase-matched generation of frequencies 70 <ν<110 cm−1 by nonlinear mixing in a birefringent ternary semiconductor, ZnGeP2. An observed power of ∼1.7 μW at 83.37 cm−1 gave a signal-to-noise ratio of ∼1000 with a Ge:Ga detector. In combination with tunable optical lasers, this technique should yield a tunable source of submillimeter wave radiation for high-resolution spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…Therefore, applications such as basic and applied physics, biological, medical, communications, and security using THz waves are anticipated [1,2]. A THz-wave source that uses a nonlinear optical (NLO) process has been achieved to realize these applications [3][4][5][6]. However, these sources were limited in their tunability by the NLO material characteristic.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, applications such as basic and applied physics, biological, medical, communications, and security using THz waves are anticipated [1,2]. A THz-wave source that uses a nonlinear optical (NLO) process has been achieved to realize these applications [3][4][5][6]. However, these sources were limited in their tunability by the NLO material characteristic.…”
Section: Introductionmentioning
confidence: 98%
“…In the early of 60', Nishizawa predicted that THz-wave would be generated via the resonance of lattice and molecular vibrations [1]. Recently, a parametric process based on second-order nonlinearities has been used to generate tunable monochromatic coherent THz-waves using nonlinear optical (NLO) crystals [2][3][4][5][6][7]. Among a way to generate THz-wave via nonlinear optical down-conversion processes, difference frequency generation (DFG) has big advantages, it is easy to tune and wide tunability and high power output could be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Both these sources of loss disappear at low temperature leaving the ultimate limit as the wing of the lowest frequency polar lattice band. ZnGeP, is the only ternary compound for which a submillimetre trai~snzission measurement has been made [25]. This showed that at room temperature ZnGeP, has a useful transmission, loss'coefficient a < 6 cm-' for wavelengths longer than 100 pm (note : cc < 3 cm-' is the more usually adopted transmission limit).…”
Section: Conductionmentioning
confidence: 99%